Work, education and out-migration among children and youth in upland Asia: changing patterns of labour and ecological knowledge in an era of globalisation - Punch, S.; Sugden, Fraser (Informa UK Limited, 2013)
In the context of ecological and economic change, this paper identifies the impact of ongoing transformations in young people's labour contribution in four natural resource-dependent regions in India, Vietnam and China. Children's work is important to maximise household labour productivity, while also endowing them with the ecological knowledge necessary to sustain key productive livelihood activities. However, today, an increased emphasis on education and the out-migration of youth is reducing their labour contribution, particularly in the more economically developed case study communities in Northern Vietnam and China. While selective in its extent, these changes have increased the labour burden of older household members and women, while the economic opportunities young people aspire to following schooling or migration frequently prove elusive in a competitive liberalised economy. Another implication of young people diverting their labour and learning away from traditional natural resource-based livelihood activities is the loss of valuable ecological knowledge.